Cutting propagation technique of mahogany (Swietenia macrophylla) in microtunnels from the Peruvian Amazon - Vallejos Torres, Geomar (2025)
Swietenia macrophylla is a forest species of great commercial value that is categorized as vulnerable in Peru. Therefore, the objective of this study is to optimize a protocol for cutting propagation of S. macrophylla using microtunnels in the San Martín, Peruvian Amazon. Three experiments were conducted: sterilization, which tested ethyl alcohol (EA), Tween-80 (T), carbendazim (CZ), and combinations; a rooting experiment with different substrates and doses of indole-3-butyric acid (IBA); and an acclimation experiment of rooted cuttings, with different shade coverage and relative humidity conditions. The lowest contamination of S. macrophylla cuttings (9.75%) was achieved with the combined EA-CZ treatment; this treatment resulted in the lowest necrosis (9.1%) and survival of 86.50%. The best responses in rooting, root biomass, and cutting survival were presented by the combination of sterilized sand with 3,000 mg L-¹ of IBA, with averages of 73.89%, 0.036 g, and 2.22 cm, respectively. The best acclimation was obtained under 80% shade and 60% relative humidity, with an average survival rate of 91.67%. The general results were successful; therefore, they could be a valuable tool for the rescue, conservation, and restoration of ecosystems with cloned S. macrophylla trees that are resilient to climate change.